2017
DOI: 10.1002/bkcs.11164
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Lysozyme Loading in Powderized Liposomes by Controlling Encapsulation Processes

Abstract: Liposomes have demonstrated great potentials as protein carriers in various pharmaceutical applications. However, low loading amount of proteins in liposomes have been a major challenge for maximizing the therapeutics potential of the proteins. We thus aimed to enhance the loading amount of a model protein, lysozyme, in liposomes by controlling key experimental variables of a reverse phase evaporation method. The loading amount of lysozyme in liposomes was evaluated with changing type of organic solvents used,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The whole LZ adsorption capacity in NMP/H2O is the highest among the three organic-solvent-aqueous solutions, which is maybe related to the polarity of the solvent. The solubility and polarity parameter of the three solvents is DMSO (26.7 MPa 1/2 , 16.4 MPa 1/2 ) > DMF (24.8 MPa 1/2 , 13.7 MPa 1/2 ) > NMP (22.9 MPa 1/2 , 12.3 MPa 1/2 ) [40]. LZ is a polarity macromolecule, and the stronger interaction between the LZ macromolecule and solvent happens when the solvent with a higher solubility and polarity LZ is a polarity macromolecule, and the stronger interaction between the LZ macromolecule and solvent happens when the solvent with a higher solubility and polarity parameter is used, which leads to the formation of more entanglements on one LZ molecular chain.…”
Section: Morphology Of Pi/hap Mmmsmentioning
confidence: 97%
See 2 more Smart Citations
“…The whole LZ adsorption capacity in NMP/H2O is the highest among the three organic-solvent-aqueous solutions, which is maybe related to the polarity of the solvent. The solubility and polarity parameter of the three solvents is DMSO (26.7 MPa 1/2 , 16.4 MPa 1/2 ) > DMF (24.8 MPa 1/2 , 13.7 MPa 1/2 ) > NMP (22.9 MPa 1/2 , 12.3 MPa 1/2 ) [40]. LZ is a polarity macromolecule, and the stronger interaction between the LZ macromolecule and solvent happens when the solvent with a higher solubility and polarity LZ is a polarity macromolecule, and the stronger interaction between the LZ macromolecule and solvent happens when the solvent with a higher solubility and polarity parameter is used, which leads to the formation of more entanglements on one LZ molecular chain.…”
Section: Morphology Of Pi/hap Mmmsmentioning
confidence: 97%
“…Kopec et al reported that the adsorption of LZ onto crosslinked PI/cation exchange particle MMMs was 27.9 mg/g [7], lower than the results obtained in this work (34.1 mg/g). Ro et al used powderized liposomes to carry LZ, and the loading amount of LZ in liposome was 5.4% at a volume ratio of aqueous to organic of 1:4 [40]. The absolute values cannot be compared to this work because the units of adsorption capacity are different.…”
Section: Morphology Of Pi/hap Mmmsmentioning
confidence: 98%
See 1 more Smart Citation